Heterocoagulation and SPS sintering of sulfonitric-treated CNT and 8YZ nanopowders - Gómez, Sofía (2019)
Reinforcement of ceramic composites using carbon nanotubes (CNT) has been extensively studied for materials such as Al2O3, Si3N4 and tetragonal ZrO2. Knowledge concerning CNT composites based on a matrix of cubic zirconia (8YZ) is in short supply, however. This paper presents a study on the addition of 1 wt% CNT to an 8YZ matrix. CNT was functionalized by sulfonitric treatment at three different temperatures: 50, 90 and 130°C. To obtain strong bond between the CNT and the 8YZ particles, the composites were produced by electrostatic heterocoagulation followed by consolidation by spark plasma sintering (SPS). Dense 8YZCNT composites were successfully processed by the proposed route. A study of the influence of the surface treatment temperature of CNT on the final properties of ceramics is also presented. CNTs are dispersed uniformly and individually within the 8YZ matrix in 8YZ-CNT 90 and 8YZ-CNT130 composites. 8YZ-CNT50 displayed a less uniform CNT distribution and the largest grain size, suggesting that the lowest temperature acid pretreatment is less effective for the subsequent heterocoagulation mixture. The reinforcement of ceramic materials by the addition of 1 wt% CNT was confirmed by an evaluation of fracture toughness.